Patterns of substance use and abuse in inner-city adolescent medical patients. - Earls, F. (Yale Journal of Biology and Medicine, 1988)
Distinct patterns of use and abuse of alcohol and illicit drugs are described in a sample of 2,415 teenage patients using primary health clinics over a two-year period. The sample was obtained in the course of a large-scale study to evaluate the effectiveness of consolidated medical programs directed to predominantly inner-city, minority-group adolescents. Information was obtained in personal interviews using a structured format and professional interviewers. Analysis of data proceeded in two steps. First, the rates of progression from abstention or light use of alcohol and drugs to regular use or abuse, and the reverse of this pattern (i.e., remission) were examined. The second step in the analysis was to examine the degree to which certain psychosocial variables characterized temporal patterns of heavy use. Regular tobacco use had a substantial influence on the progression to substance abuse in male and female patients. The results indicate that about 20 percent of the patients attending these clinics were in some phase of either increasing or decreasing their substance use, and another 20 percent engaged in regular use continuously over the two-year period, while the remaining 60 percent of patients stayed at low risk over this same period. These subgroups were rather easy to differentiate on the basis of concurrent behavioral and lifestyle problems.